The Role of The Head of the Office in Implementing the Bureaucratic Reform Integrity Zone (ZI-RB) in the Office Kementerian Agama Kabupaten Tanah Datar - Afri Yona; Husnani Husnani; Vicky Rizki Febrian; Jamilus Jamilus (Jurnal Manajemen Pendidikan Islam (MANAPI), 2022)
The main problem in this thesis is about the role of the Head of Office in Implementing the Bureaucratic Reform Integrity Zone (ZI-RB) at the Office of the Ministry of Religion of Tanah Datar Regency. The purpose of this study was to find out how the role of the head of the office in implementing the integrity zone of bureaucratic reform and how the division of duties of employees at the Office of the Ministry of Religion of Tanah Datar Regency.The type of research that the author uses is a type of field research or field research, to obtain data from the problems studied. The data collection technique of this research was obtained from the results of observations, interviews and documentation. The data analysis technique that the writer uses is data reduction, data presentation, conclusion drawing and verification. The technique of guaranteeing the validity of the data that the author uses is persistence of observation, triangulation and using reference materials, then describes and classifies certain aspects of the problem and describes it through effective sentences.Based on research conducted in the field on the role of the head of the office in implementing the Bureaucratic Reform Integrity Zone at the Office of the Ministry of Religion of Tanah Datar Regency, the head of the office has shown his role well and has done according to his ability in carrying out activities to make the office an integrity zone of bureaucratic reform. In addition, the head of the office has demonstrated his interpersonal, informational, decision-making and supervisory roles well.Keywords : The Role Of The Head Of The Office In Implementing The Bureaucratic Reform Integrity Zone (Zi-Rb) In The Office Kementerian Agama Kabupaten Tanah Datar